Influence Of Experiential Marketing And Customer Relationship Management During Pandemic On Restaurant Service User Loyalty - Adelia Destya Sari; Eka Askafi (Universitas Islam Kadiri, 2021)
The problem of this research is about the effect of experiential marketing, customer relationship on loyalty through satisfaction as an intervening variable. In this study, the population was all customers of Damarmas resort as many as 115 people within 3 months of the study. The number that was sampled at the time of the study started from March 2021 to June 2021, with a quantitative approach through path analysis. The results of this study indicate that Experiential marketing (X1) has a positive and significant effect on satisfaction (Z) Because the significance value is <0.05, this means that H1 is accepted. Customer Relationship Management (X2) has a positive and significant effect on satisfaction (Z) because the significance value is <0.05, this means that H2 is accepted. Experiential marketing (X1) has a positive and significant effect on loyalty (Y) because the significance value is <0.05, this means that H3 is accepted. Customer Relationship Management (X2) has a positive and significant effect on loyalty (Y) because the significance value is <0.05, this means that H4 is accepted. Satisfaction (Y) has a positive and significant effect on loyalty (Y), because the significance value is <0.05, this means that H5 is accepted indirectly. Experiential marketing (X1) through Satisfaction (Z) has a significant effect on Loyalty (Y). Indirectly, Customer Relationship Management (X2) through Satisfaction (Z) has a significant influence on Loyalty (Y).